Analysis of Burnup effects and Its Integrity Assessment in the Interim of Irradiation with Molecular Dynamics. (2020) - Willie, Ahli K.D.; Zhao, Hongtao; Azeem, M. Mustafa; Svetlana, Teplinskaya
Abstract: Burnups can cause major structural changes in the edge of the fuel rod and a general degradation of the thermal conductivity. In irradiated mixed oxide fuels of UO2, PuO2 with NpO2 as fission products (FP) various chemical states depending on the conditions of the fuel is developed. This work, we firstly applied the MD relation to obtain the thermal conductivity of UO2, PuO2, and (U, Pu) O2 in temperature range of 300–2000 K. Lattice parameter, Burnup and the thermal conductivity were then calculated for specified UO2 and PuO2 . This calculation relates the degradation of thermal conductivity with a number of pores and increasing temperature. Finally, the migration energy barrier and the recovery energies of the obstruction type defects were calculated with molecular dynamics simulation.